Mrs. B's guide to household witchery : everyday magic, spells, and recipes - Bradley, Kris (Weiser Books, 2012)
For domestic goddesses everywhere--add some magic and fun to those mundane household chores with Mrs. B.'s Guide to Household Witchery. Whether you're sweeping the floor, making a meal, or cleaning out that junk drawer, domestic witch Kris Bradley, creator of the popular blog, Confessions of a Pagan Soccer Mom, will show you how to create spells and magic to bring happiness and balance into your home.